Hubungan Orang Tua dan Guru dalam Mencegah Bullying - Hakim, Nur; Dewi, Ririn Nurlafika; Herianingtyas, Nur Luthfi Rizqa (Awwaliyah: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2023)
This study aims to understand the perspectives of parents and teachers regarding their roles in preventing bullying, as well as to identify the strategies they use in collaboration. This research uses qualitative methods to explore the relationship between parents and teachers in preventing bullying cases in elementary schools. The role of parents and teachers is very important to prevent bullying. Therefore, parents and teachers should have a similar understanding of the importance of cooperation or collaboration in preventing bullying. Parents and teachers should also realize that the responsibility of preventing and overcoming bullying does not lie solely with one party, but requires close cooperation.